Integrating Islamic Ethics Into Pro-Environmental Behaviour: A Systematic Literature Review And Proposed Conceptual Framework - Eko Susanto; Siti Hafsah Zulkarnain (Integrasi Sains Media, 2026)
The integration of Islamic ethics into pro-environmental consumer behavior has emerged as a rapidly expanding research domain; however, extant frameworks remain fragmented. This study aims to synthesize global literature on green consumption within an Islamic context through a Systematic Literature Review (SLR). Utilizing the PRISMA 2020 protocol, 78 Scopus-indexed articles published between 2015 and 2025 were analyzed to identify theoretical antecedents and behavioral barriers. The findings propose the Integrated Islamic Green Behavior Model (IIGBM), which incorporates three primary structural pathways: the Stewardship Pathway (Khalifah), the Balance Pathway (Mizan), and the Wholesomeness Pathway (Thayyib). The analysis reveals a significant